Pedestrian User-Friendly Intelligent Crossing Advance For Improved Safety - Ahmad, Rahmat; Wahyu Hidayat, Dwi; Oktavianus Sasue, Riz Rifai; Soimun, Ahmad; Prima Gilang Rupaka, Anggun; Oktopianto, Yogi; Budi Sulistyo, Aris (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2022)
The habit of pedestrians in using the road when crossing the road is in the spotlight because it will cause traffic jams so that they are prone to accidents. No road user wants to experience such an accident, whether it is a minor accident or an accident that is fatal and leads to death. Pelican crossings are made to minimize pedestrian accidents, but this facility does not guarantee that accidents will not occur. Problems arise when pressing the crossing button will create congestion and noise due to the notification sound of the crossing. When someone wants to cross it will result in the accumulation of vehicles around because they are waiting for irregular pedestrians to cross. The purpose of this research is to design a pedestrian Puffin Crossing advance simulation that is more adaptive and safe. The research was conducted by making a prototype using a microcontroller and several sensors which will later be used as a medium for interaction between drivers and pedestrians. The results of the prototype research can work well and in accordance with the function of each component. The recommended minimum number of pedestrians is 4 waders, the minimum required waiting time is 5 seconds, while the crossing time is conditioned based on pedestrian sensor readings at the zebra cross.